The Influence of the Principal's Leadership Style on Increasing Teacher Performance at SMK Negeri 1 Tulung Selapan - Gelisa Gelisa; Muhammad Wadud; M Kurniawan DP (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to investigate how the influence of the principal's leadership style on teacher performance at SMK NEGERI 1 Tulung Selapan. The sample used in this study was 55 respondents. Data collection techniques using questionnaires, interviews, documentation. The analysis used was by testing the reliability data, t-test, correlation, hypotension test, simple linear test, correlation coefficient test (r), coefficient of determination (r2). The results of the study prove that the Leadership Style affects teacher performance by 29.54%. R Square of 0.141 or 14.1% indicates that the variable of teacher performance that can be explained by leadership style is 14.1% while 0.859 or 85.9% is explained by other factors not explained by this study. Based on the results of a simple linear analysis of Leadership Style on Teacher Performance, the constant value (a) is 21.082 and the Leadership Style (X) has a regression coefficient of 0.268 so Y = 21.082 + 0.268X, thus Y = 21.35.